The Influence of Brand Image and Online Customer Reviews on Purchase Intention in Shopee Live Streaming Shops with Trust as a Mediating Variable in Bengkulu City - Fachriansyah, Aditya (Universitas Bengkulu, 2023)
The aim of this research is to determine and analyze brand image, customer reviews, trust, purchase intention, and the mediating influence of trust on brand image, customer reviews, on purchase intention. This research uses quantitative methods using primary data obtained by distributing questionnaires online via social media as well as friends and family. The non-probability sampling technique used in this research is purposive sampling as a sampling method. The number of samples in this study was 250 respondents who had used Shopee live streaming in Bengkulu City. Then the data obtained was processed using the Structural Equation Modeling (SEM) method with the help of the SmartPLS 3.0 application. SmartPLS 3 was used to analyze data collected from online questionnaires. The results of this research show that: 1) Brand Image can have a positive and significant effect on Purchase Intention. 2) Customer reviews can have a positive and significant effect on Purchase Intention. 3) Trust has a positive and significant effect on Purchase Intention. 4) Brand image has a positive and significant effect on Trust. 5). Customer Reviews can influence Trust positively and significantly. 6). Trust can mediate the relationship between Brand Image and Purchase Intention. 7). Trust can mediate the relationship between Customer Reviews and Purchase Intention. Practical advice in this research is for shopee shop live streaming application developers, they can continue to maintain their brand image and customer reviews, so they can continue to innovate and maintain the quality of their products that online customer reviews continue to increase and make other consumers interested see them buying products via the Shopee live streaming application.